Urban and school segregation in Paris: The complexity of contextual effects on school achievement: The case of middle schools in the Paris metropolitan area - Oberti, Marco; Savina, Yannick (Urban Studies, 2019)
In French cities, because of a rigid school catchment area policy based on students’ place of residence, there is a strong correlation between socio-residential segregation and school segregation. But the latter is not merely a simple, mechanical reflection of the former. Many processes (the choice of private schools or of specific and very often selective and rare curricula that make it possible to avoid the local public middle school; disability; siblings; personal convenience) contribute to exacerbating the correlation. Using data from the Ministry of Education, the current paper develops a typology of middle schools according to their socio-economic composition (using Correspondence Analysis and Hierarchical Agglomerative Classification), and looks at their unequal spatial distribution across the Paris metropolitan area. We measure school segregation using classical indices, and show that school segregation is higher than socio-residential segregation, particularly for students from upper-middle class backgrounds and for students from working class backgrounds. The spatial analysis of segregation, when compared with test scores, reveals strong inequalities between locations. The impact of school segregation on school success has been mainly analysed in terms of the effect of students’ social background. If one looks at the number of top tier marks (‘mention bien et très bien’) obtained at the final middle school exam in the Paris metropolitan area from 2006 to 2012, it is possible to see that girls and boys are not equally sensitive to these contextual effects. Based on logistic regressions, the analysis of the interactions between individual characteristics (socio-economic background and gender) and contextual variables (the school’s status [private/public], its location, its socio-economic composition) gives a more complex picture. This raises both methodological and political questions that suggest the need for an intersectional approach. Such a finding presents a challenge not only for social scientists studying segregation and school inequalities, but also for policy makers who want to reinforce mixed schooling.
Keywords: Paris metropolitan area; school achievement; school segregation; social mix; urban segregation; 城市隔离; 学校成绩; 学校隔离; 巴黎大都市区; 社会混合